(untitled) (Patan Pragya, 2020)
Malnutrition among children stands as a serious problem to child growth and development and it leads to child morbidity and mortality. This study has tried to find the status of malnutrition among below five years children in Nepal based on the secondary data from Nepal Demographic and Health Survey (NDHS) 2006, 2011 and 2016. Study found out that 36 percent children were stunted in 2016 while 49 percent in 2006. On the other hand wasted has slowly decreased during the ten years period. Results also showed that those mothers who were thin have higher level of stunting, wasting and underweight than those having a normal Body Mass Index (BMI). Study found out that in 2016 more than half children were anemic while the percent was 48 in 2006 and 46 in 2011. To eradicate the level of malnutrition among children and overall development of the country, it is necessary to launch broader platform on nutritional intervention and should be focused at community and region based malnutrition programs.